Deconstructing the Language Poetry in Some Selected Poems of Charles Bernstein From a Derridaian Perspective (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This paper investigates the language poetry and its practice in some poems of the American poet Charles Bernstein. The study will examine several poems for Bernstein, like "April" and "March" from Stigma, "Locks without Doors" from Dark City, "Slowed Reason" from Rough Trades, "Lift off", and "The next Available Place". It argues that the Derridaian perspective plays a prominent role in the way Bernstein visualizes meaning in his poetry. According to Jacques Derrida (1993), the divergence of indicative communication by making intentional gaps between expression and indication creates the signification to difference, deviation, and departure. The gaps for Derrida are gaps of space which become gaps of time and those of time become gaps of space, adding that the gaps of difference are in themselves gaps as difference. The gap itself works for the auto production and the auto-determination of meaning which will keep on travelling.The study will analyse the language of Bernstein in the above mentioned poems to prove that meaning emerges through interpretation and that even authors do not control the text interpretation, and that texts, like language itself, have no outside referents or transcendental signified.
Keywords: Deconstruction; Language Poetry; Indicative System of Communication; Jacques Derrida; Gaps of Space and Time; Gaps of Difference